EFFECTS OF PROGRAM APPLING THAI TRADITIONAL MEDICINE WITH SELF-EFFICACY THEORY ON HEALTH BEHAVIORS OF TYPE 2 DIABETIC PATIENTS IN PHANTHONG HOSPITAL CHONBURI PROVINCE - ถาวรสิน พัชรภรณ์; ใจดี วัลลภ (Primary Health Care Journal (Northeastern Edition), 2025)
Diabetes mellitus is a chronic disease and a significant global public health problem. In Thailand, the prevalence among individuals aged 15 years and older has been continuously increasing. Without proper care, diabetes can lead to complications in multiple body systems. This quasi-experimental study aimed to examine the effects of an integrated program combining Thai traditional medicine with the Self-Efficacy Theory on the health behaviors of patients with type 2 diabetes. A purposive sample of 60 uncontrolled type 2 diabetic patients was randomly assigned into an experimental group (n=30) and a comparison group (n=30). The experimental group participated in an 8-week intervention program, while the comparison group received standard health education. Data were collected using questionnaires and analyzed using Independent Samples t-test and Paired Sample t-test. The findings revealed that the experimental group showed statistically significant improvements in diabetes knowledge, self-efficacy, self-care behaviors (p < 0.001), and a significant reduction in blood glucose levels compared to both pre-intervention and the comparison group (p < 0.001). The study suggests that applying Thai traditional medicine principles integrated with Self-Efficacy Theory effectively enhances health behaviors and glycemic control among type 2 diabetic patients, supporting improved quality of life.